(3efgL JOHQ GdbQBf GdcQje (B/s - (3jGSjf, MceJ HTjQ,s 1955- ((3GdQjGV (B:s (3OGQ GdMVGQI ddfTQ hGdJhRjY,s, 2004)
(3jJfGhd cJGH (B((3efgL JOHQ GdbQBf GdcQje(B) (3hGdPj bGe HJCdjag O(B. (3MceJ Hf HTjQ jGSjf, ehVhY (B((3GdbQBf GdcQje(B) (3gPG GdcJGH jYGdL aj GdCSGS bVjI JOHQ GdbQBf GdcQje, hGdhSGFd GdeSGYOI Ydi Pdc; EP Cf JOHQ GdbQBf GdcQje gh GdSHjd GdCbhe ddYed HeG ajg, hgh GdSHjd GdCQTO dJMUjd NjQj GdOfjG hGdBNQI(B. (3hCf ef Cge CgOGa GdJOHQ gj eYQaI CMcGe GdbQBf GdcQje dHjGf GdMdGd hGdMQGe(B. (3hbO JfGhd GdeDda ehVhY cJGHg ef NdGd LedI ef GdYfGhjf GdaQYjI, HdZJ fMh SHY hYTQjf YfhGfG(B. (3hbO UGZ GdeDda eGOI cJGHg HdZI SgdI, hCSdhH hGVM, NGd ef GdJYbjO(B. s
Keywords: (3GdbQBfs -- (3eHGMK YGeIs